Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To solve the equation [tex]\( 27 = 9^{x-1} \)[/tex], let's proceed through the steps in a detailed manner:
1. Express 27 and 9 as powers of the same base:
We know that 27 can be written as [tex]\( 3^3 \)[/tex] and 9 can be written as [tex]\( 3^2 \)[/tex].
So we can rewrite the equation:
[tex]\[ 3^3 = (3^2)^{x-1} \][/tex]
2. Simplify the right side of the equation:
Using the property of exponents, [tex]\((a^m)^n = a^{mn}\)[/tex], we can simplify the right-hand side:
[tex]\[ (3^2)^{x-1} = 3^{2(x-1)} \][/tex]
Thus, the equation becomes:
[tex]\[ 3^3 = 3^{2(x-1)} \][/tex]
3. Equate the exponents:
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ 3 = 2(x-1) \][/tex]
4. Solve for [tex]\( x \)[/tex]:
a. First, distribute the 2 on the right side:
[tex]\[ 3 = 2x - 2 \][/tex]
b. Add 2 to both sides of the equation to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ 3 + 2 = 2x \][/tex]
[tex]\[ 5 = 2x \][/tex]
c. Finally, divide both sides by 2 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{5}{2} \][/tex]
[tex]\[ x = 2.5 \][/tex]
Thus, the solution to the equation [tex]\( 27 = 9^{x-1} \)[/tex] is:
[tex]\[ x = 2.5 \][/tex]
1. Express 27 and 9 as powers of the same base:
We know that 27 can be written as [tex]\( 3^3 \)[/tex] and 9 can be written as [tex]\( 3^2 \)[/tex].
So we can rewrite the equation:
[tex]\[ 3^3 = (3^2)^{x-1} \][/tex]
2. Simplify the right side of the equation:
Using the property of exponents, [tex]\((a^m)^n = a^{mn}\)[/tex], we can simplify the right-hand side:
[tex]\[ (3^2)^{x-1} = 3^{2(x-1)} \][/tex]
Thus, the equation becomes:
[tex]\[ 3^3 = 3^{2(x-1)} \][/tex]
3. Equate the exponents:
Since the bases are the same, we can set the exponents equal to each other:
[tex]\[ 3 = 2(x-1) \][/tex]
4. Solve for [tex]\( x \)[/tex]:
a. First, distribute the 2 on the right side:
[tex]\[ 3 = 2x - 2 \][/tex]
b. Add 2 to both sides of the equation to isolate the term with [tex]\( x \)[/tex]:
[tex]\[ 3 + 2 = 2x \][/tex]
[tex]\[ 5 = 2x \][/tex]
c. Finally, divide both sides by 2 to solve for [tex]\( x \)[/tex]:
[tex]\[ x = \frac{5}{2} \][/tex]
[tex]\[ x = 2.5 \][/tex]
Thus, the solution to the equation [tex]\( 27 = 9^{x-1} \)[/tex] is:
[tex]\[ x = 2.5 \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.